Immune-Related Long Non-coding RNA Signature and Clinical Nomogram to Evaluate Survival of Patients Suffering Esophageal Squamous Cell Carcinoma - Zhu, Ting; Ma, Zhifeng; Wang, Haiyong; Wei, Desheng; Wang, Bin; Zhang, Chu; Fu, Linhai; Li, Zhupeng; Yu, Guangmao (Frontiers in Cell and Developmental Biology, 2021)
Esophageal squamous cell carcinoma (ESCC) turns out one of the most prevalent cancer types, leading to a relatively high mortality among worldwide sufferers. In this study, gene microarray data of ESCC patients were obtained from GEO database with the samples involved in divided into training set and validation set. Based on the immune-related differential lncRNAs we identified, a prognostic 8-lncRNA-based risk signature was constructed following regression analyses. Then, the predictive capacity of the model was evaluated in the training set and validation set using survival curves and receiver operation characteristic curves. In addition, univariate and multivariate regression analyses based on clinical information and the model-based risk score also demonstrated the ability of the risk score in independently determining the prognosis of patients. Besides, based on the CIBERSORT tool, the abundance of immune infiltrates in tumor samples was scored, and significant difference was presented between the high- and low- risk groups. Correlation analysis with immune checkpoints (PD1, PDL1, CTLA4) indicated that the 8-lncRNA signature-based risk score was negatively correlated with PD1 expression, suggesting that the 8-lncRNA signature may make an effect in the immunotherapy for ESCC. Finally, GO annotation was performed for the differential mRNAs that were co-expressed with the 8 lncRNAs, and it was uncovered that they were remarkably enriched in immune-related biological functions. These results suggested that the 8-lncRNA signature-based risk model could be employed as an independent biomarker for ESCC prognosis and might play a part in evaluating the response of ESCC to immunotherapy with immune checkpoint blockade.